Establishing monetary union in the Gulf Cooperation Council: What lessons for regional cooperation? - Shinji Takagi (Asian Development Bank Institute (ADBI), 2012)
The paper reviews the experience of regional economic cooperation in the Gulf Cooperation Council (GCC). Conceived as a regional security alliance, the GCC has evolved to become a common market in the making. All six GCC countries participate in the common market project, and additional countries may join. But the timing of introducing a common currency, initially targeted for 2010, remains uncertain, especially in the light of the ongoing euro area crisis. Two countries have withdrawn from the common currency project; another has ceased to comply with a prerequisite for entering the monetary union. But the GCC is not the same as the GCC Monetary Union, nor should the success of the GCC be judged solely on the basis of how many member states end up participating in the single currency. From the standpoint of Asia, the contrast appears striking. In Asia it has been a slow and difficult process to form consensus on regional cooperation, but political agreement collectively to promote economic integration was reached rather quickly in the GCC. Even so, regional institution building, especially in creating regional decision-making bodies, has been slow in the GCC; the region is yet to see the degree of economic integration already experienced in Asia. An important lesson of the GCC experience is that political will and leadership alone is not a sufficient condition for success. What ultimately determines the success of any regional cooperation effort is the willingness of countries to surrender part of their national sovereignty, a difficult feat for any group of countries.
Keywords: F15; F36; F55; O53; 330; monetary union; gulf cooperation council; regional cooperation; common market; common currency; single currency; euro area; Währungsunion; Internationale Wirtschaftspolitik; Wirtschaftsintegration; Arabische Golf-Staaten